Secondary School English Teachers’ Viewpoints Towards the Implementation of Kurikulum Merdeka - Rakhmawati, Rakhmawati; Imaniar, Fahmy (Department of English Language Education, UIN Sunan Ampel Surabaya, 2024)
The curriculum reform encourages all schools in Indonesia to gradually adapt and try to use Kurikulum Merdeka although many of them are still implementing the 2013 curriculum. This study aims at investigating the secondary school English teachers’ viewpoints toward Kurikulum Merdeka. Through a qualitative approach, this study brings up the urgency of the teacher's voice as the ones implementing the curriculum in the practical field. Drawing upon data collected by means of questionnaires and interviews, this study reveals a multi-dimensional structure of teachers’ viewpoints. There are 13 teachers being involved in this study from 13 different secondary schools. They were purposively chosen as they are partner schools of English Language Education Department UIN Sunan Ampel Surabaya having adequate assets for implementing Kurikulum Merdeka-based learning. There are several main themed viewpoints found through this study which deals with the understanding of the curriculum, the implementation and the barriers encountered and the current needs. First, teachers mostly know the terms related to Kurikulum Merdeka but they do not exactly know the meaning. Another viewpoint is that the teachers whose school have tried to implement Kurikulum Merdeka partly, have issues in designing the Teaching Module and formulating the elements within the Teaching Module. Some of them have actualized the Teaching Module into real practice and issues dealing with it emerged as they implement it. The study leads to the urgency of training on designing and implementing Kurikulum Merdeka for the teachers, especially those from private schools.